2009
DOI: 10.1007/s00234-009-0502-2
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular occlusion of intracranial wide-necked aneurysms with stenting (Neuroform) and coiling: mid-term and long-term results

Abstract: Our results demonstrate the effectiveness of the technique, a small rate of procedural complications, and long-term tolerance of the Neuroform Stent. Despite some evidence of early aneurysmal recurrence, long-term durability of stent-assisted aneurysm occlusion is stable after the first year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
56
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(65 citation statements)
references
References 29 publications
6
56
1
2
Order By: Relevance
“…When the Guglielmi detachable coil procedure was first introduced in the literature, it was reported that total aneurysm occlusion could be achieved in only 15% of wide-neck aneurysms 6) . Sedat et al 22) reported that long-term complete aneurysmal occlusion was obtained in 71% of wide-necked aneurysms using stenting and coiling. Additionally, Raymond et al 20) treated 501 aneurysms with detachable coils only and reported that recurrences were found in 33.6% of treated aneurysms at mean of 12.31 months follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the Guglielmi detachable coil procedure was first introduced in the literature, it was reported that total aneurysm occlusion could be achieved in only 15% of wide-neck aneurysms 6) . Sedat et al 22) reported that long-term complete aneurysmal occlusion was obtained in 71% of wide-necked aneurysms using stenting and coiling. Additionally, Raymond et al 20) treated 501 aneurysms with detachable coils only and reported that recurrences were found in 33.6% of treated aneurysms at mean of 12.31 months follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…With this, it was possible to overcome the technical difficulty of endovascular treatment. In recent years, the use of stent-assisted coil placement has been reported by several researchers 1,3,13,22) , and from these reports, it seems that the stent is a very helpful device which facilitates the endovascular treatment of wide-necked intracranial aneurysms. However, the stent-assisted method is subject to limitations 1,7,13) .…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6] The role of these devices in the treatment and prevention of ischemic and hemorrhagic strokes continues to expand, as has recognition of the importance of assessing the relationship between an implanted device and its host vessel for acute periprocedural success and for long-term biologic response. Such devices are fabricated from metal alloys, typically nickel-titanium (nitinol), platinum, or cobaltchromium, and have strut or filament diameters of Ͻ75 msubstantially smaller than those of stents designed for coronary and carotid applications.…”
mentioning
confidence: 99%
“…[1][2][3] Particularly for saccular aneurysms with broad necks and short domes, stent-assisted coiling has become a common technique. [4][5][6][7][8] Prior studies have reported that stent-coiling may result in less aneurysm recanalization over time but more complications-both intraprocedurally and in a delayed fashion-than coiling alone. [9][10][11][12][13] A recent large, single-institution, retrospective series described higher morbidity and mortality rates associated with the stent-coiling technique as compared with coiling either with or without balloon assistance.…”
mentioning
confidence: 99%